Recobrimento de sementes silvestres em panela rotatória - Rosso, Giovana Américo (2013)
In order to minimize the effects caused by the development of Brazil, such as the suppression of riparian forest, one has searched for tree species that have the characteristics needed for the recovery of degraded areas. Given this, studies focus on higher plants of encapsulated wild fruits, especially the Mabea fistulifera Mart. Considering that M. fistulifera reproduces through embryonic units that need to be treated, this study aimed to evaluate the drying of wild fruits with explosive dehiscence and the coating "in natura" seed with gel mixture via coating pan, as well as evaluating the tolerance of embryos related to the immediate effects of the processes. Thus, the experimental procedure consisted of the collection of capsular fruits and extraction of seeds of fruit by drying so were analyzed drying methods via radiation, natural convection, forced convection and coating pan. It was considered for the drying methods analysis the opening fruit speed and seed vigor. Thus, all processes allowed physiological recovery of embryos, but the extraction method via pan promoted the highest opening speed of the fruits. Once performed the extraction, the seeds were separated from the inert material obtaining pure batches of seeds. There were also characterizations of size, shape and specific mass obtaining the results (0,78±0,05) cm, (0,67±0,04) cm and (0,59±0,04) cm for Dmax, Dmédio and Dmim, respectively, form factor (0,75±0,01), specific mass of (1,20±0,01) g/cm³ and apparent mass of (0,82±0,01) g/cm³. Analyzes were also made for chemical seed yielding (82,93±0,11)% of dry matter (19,03±0,78)% crude protein, (1,18±0,11) g/kg calcium (0,65±0,03) g/kg magnesium (0,58±0,04) g/kg phosphorus (13,45±0,33) g/kg potassium (0,70±0,03) g/kg of sulfur. The process of coating seeds, through reaction between sodium alginate gel and calcium chloride salt at different angles of inclination and rotation speed of the coating pan, was also analyzed. Thus, it was found that to achieve the coating of the particles it was necessary to prepare the particle surface by chemical scarification, in order to increase the surface roughness of the seed, followed by rehydration with saturated calcium chloride. This way, it was found that the angle of 25° and speed of 25 rpm generate the greatest quantity of mass adhered on seeds. In addition, tests were performed to verify the efficiency of the coating process, and with the lowest angle set in experimental design was found higher values of efficiency. In tests of particle growth was evaluated that the process time was approximately 8 seconds. Finally, the analysis and processing of data obtained through statistical techniques and equations from literature were performed. In this way, the results contributed to improvements in drying processes of wild fruits and the coating of seeds of the pioneer species M. fistulífera.